(3Jbhje GdCHOGf aj JOHjQ GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s ((3GdbSWfWjfI s)
(3ChdgG (B:s
(3hEPG cGf JOHjQ GdUMI GdebUhO ai faSg hdG jWdH dYjfI hEfeG jWdH ddeecf ef GdYde hGdYded agh cGdNGOe dgeG s
(3BNQgG (B:s
(3hai bGfhf GdeOGhGI Cf GdOhGA jfHZi Cf jhUd Edi GdYVh GdeOGhi ef CbQH GdehGVY Edjg abO JbOe JaUjd Pdc hGdcdGe Ydjg haSGO WQjbge Edjg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B64 s
Keywords: (3GdWHs